[Lys3, Lys4] M-PONTX-Dq3a [1–15]: a selective dinoponeratoxin-derived peptide that disrupts parasite membranes and inhibits TcGAPDH activity in Trypanosoma cruzi - Evelline Araújo Edson; Emanuel Paula Magalhães; Márcia Machado Marinho; Emmanuel Silva Marinho; João Victor Serra Nunes; Ramon Róseo Paula Pessoa Bezerra de Menezes; Alice Maria Costa Martins (Toxicon, 2026)

Evaluation of the antimicrobial and NorA and MepA efflux pump inhibitory activity of a hydrazone derivative of hydralazine against Staphylococcus aureus - Karla Susanna Tavares Grangeiro Belém; Janaina Esmeraldo Rocha; Ana Joyce Morais Bento; Jaiza Maria Lima Dias; Henrique Douglas Melo Coutinho; Francisco das Chagas Lima Pinto; Ramon Róseo Paula Pessoa Bezerra de Menezes; Mateus Edson da Silva; Emmanuel Silva Marinho; Marcia Machado Marinho; Hélcio Silva dos Santos (Archives of Microbiology, 2026)

Structural control and geometric characterization of a hydrothermal vent complex using seismic data, Potiguar Basin – Brazil - Lorenna Sávilla Brito Oliveira; Luiza Cavalcante Vinhas Lucas; David Iacopini; Fabrizio Balsamo; Anita Torabi; Behzad Alaei; João Felipe de Sousa Neto; Pedro Edson Face Moura; David Lino Vasconcelos; Vincenzo La Bruna; Francisco Hilário Rego Bezerra (Journal of South American Earth Sciences, 2026)

Rethinking expertise on climate cooling technologies - María Inés Carabajal; Aylén Bavosa Castro; Edson Bezerra; Eduarda Calado Barbosa; Camillo Fiore; Gian Franco Lisanti; Guillermo Marín Penella; Julieta Nasi; Gabriela Raggio; Julia S. Guivant; Sophie Haines; Thomas Douglas; et al. (Environmental Science & Policy, 2026)

Residual effect of silicate fertilization on ratoon sugarcane under water deficit conditions: plant biomass, nutrient element concentrations, and Si:C:N:P stoichiometric ratios - Steffany Daiana da Costa Berto; Fabiano Simplicio Bezerra; José Edson Florentino de Morais; Lucas Yago de Carvalho Leal; Martha Katharinne Silva Souza Paulino; Cicero Aparecido Ferreira Araújo; Bruce Schaffer; Clístenes Williams Araújo do Nascimento; Edivan Rodrigues de Souza (Plant and Soil, 2026)
Background and objectives Silicon (Si) has been widely reported to enhance tolerance to abiotic stresses, including drought, in several crops. However, the long-term effects of soil-applied Si remain insufficiently explored. This study aimed to assess dry matter production, plant nutritional status, C:N:P:Si stoichiometry, and soil Si availability in ratoon sugarcane under water deficit and the residual effect of an amorphous silica-derived fertilizer (ASF). Methods Ratoon sugarcane was grown under two levels, 40% or 80%, of maximum water retention capacity (MWRC) and four residual Si rates (0, 78, 117, and 156 kg ha⁻ 1 ) applied in the previous cycle. Biomass production, leaf nutrient concentrations, uptake of Si and macronutrients (N, P, K, Ca, Mg, and C) and, C:N:P:Si stoichiometric ratios, and soil Si concentrations were determined. Results The 80% MWRC treatment combined with 156 kg ha⁻ 1 promoted increases of 34% in leaf and 78% in stalk dry matter relative to the 40% MWRC treatment. Leaf Si concentration rose from 2.47 to 6.64 g kg⁻ 1 between 0 and 156 kg ha⁻ 1 . At 40% MWRC, the 156 kg ha⁻ 1 Si rate increased leaf N and P concentrations by 27% and 84%, respectively, compared with the control. The lowest soil Si concentrations were observed in the soil 15–30 cm layer, with mean values of 9.76 and 10.22 mg dm⁻ 3 under 40% and 80% MWRC, respectively. Conclusion Residual Si significantly improved biomass production and leaf nutritional status of ratoon sugarcane under water deficit. The nutrient extraction and export sequence for cultivar RB041443 was K > N > Si > Ca > P > Mg.

TcGAPDH peptidic inhibitors derived from dinoponeratoxin M-PONTX-Dq4e with trypanocidal effect - Emanuel Paula Magalhães; Dânya Bandeira Lima; Evelline Araújo Edson; Brenna Pinheiro Silva; Márcia Machado Marinho; Emmanuel Silva Marinho; Vani Xavier Oliveira; Ramon Róseo Paula Pessoa Bezerra de Menezes; Alice Maria Costa Martins (Toxicon, 2026)

Encapsulation of slow-release urea in stearic acid microspheres: Effects on nutrient digestibility, nitrogen utilization, and performance in lambs - Everton C. de. Medeiros; André L. da Silva; José Morais Perreira Filho; Kevily H. de O.S. de Lucena; Gildênia A. Pereira; Mônica T. Cavalcanti; Juliana P.F. de Oliveira; Elzania S. Pereira; Edson C. Silva Filho; Leilson R. Bezerra (Animal Feed Science and Technology, 2026)

Chemical characterization, nutritional profile, and cytotoxicity potential of Amazonian Theobroma sylvestre Mart. fruits - Edson Queiroz da Fonseca Júnior; Daniel de Queiroz Rocha; Edinilze Souza Coelho Oliveira; Samuel Oliveira da Silva; Francisca das Chagas do Amaral Souza; Gabriela Furlaneto; Laura da Silva Cruz; Luciana Azevedo; Renilto Frota Corrêa; Edgar Aparecido Sanches; Pedro Henrique Campelo; Jaqueline de Araújo Bezerra (Food Bioscience, 2025)

Preparation of novel iron-bearing biochar derived from Calotropis procera biomass for aromatic organic pollutant removal via persulfate activation - Joyce Azevedo Bezerra de Souza; Luana Rabelo Hollanda; Larissa Sobral Hilário; Raoni Batista dos Anjos; Guilherme Luiz Dotto; Edson Luiz Foletto; Osvaldo Chiavone-Filho (Environmental Science and Pollution Research, 2025)

Silicon Mitigates the Effects of Water Deficit in Ratoon Sugarcane and Enhances Leaf Water Potential, Osmotic Adjustment, and Biomass Production - Steffany Daiana da Costa Berto; Fabiano Simplicio Bezerra; José Edson Florentino de Morais; Lucas Yago de Carvalho Leal; Martha Katharinne Silva Souza Paulino; Cicero Aparecido Ferreira Araújo; Wellinton Julio Ferreira Gonçalves; Clístenes Williams Araújo do Nascimento; Edivan Rodrigues de Souza (Journal of Plant Growth Regulation, 2025)

Effects of dietary supplementation with slow-release urea coated with carnauba wax on intake, ingestive behavior, selectivity, ruminal parameters, performance and carcass traits of lambs - Tainan da Silva Batista; Leilson R. Bezerra; Pedro H.S. Mazza; Analivia M. Barbosa; Beatriz S.C. de Castro; Melissa D. Ferrer; Ana Carolina Ferreira; Jasiel S. de Morais; Edson C. da Silva Filho; Ronaldo L. Oliveira (Small Ruminant Research, 2025)

Biometric and carcass analysis of lambs fed with forage palm silage and cottonseed cake - Iara Tamires Rodrigues Cavalcante; Wandrick Hauss de Sousa; Paulo Sérgio de Azevedo; Neila Lidiany Ribeiro; Rodrigo Couto Santos; Felipe Queiroga Cartaxo; João Paulo de Farias Ramos; Marcílio Fontes Cézar; Danillo Marte Pereira; Edson Mauro Santos; Juliana Silva de Oliveira; Marcos Vinícius da Silva; et al. (Small Ruminant Research, 2025)

Current knowledge on the cave fungi in Brazilian biomes - José Fredson da Silva Alves dos Prazeres; Enrico Bernard; Cristina Maria de Souza-Motta; Diego de Medeiros Bento; Edson Nilton de Moura Silva-Júnior; Eder Barbier; Emily Oliveira Fonseca; Joenny Maria da Silveira de Lima; João Lucas Vitório Ribeiro Carvalho; Lorena Souza Miranda; Olinto Liparini Pereira; Renan do Nascimento Barbosa; et al. (Fungal Biology Reviews, 2025)

Cytotoxicity and genotoxic impacts of LAPONITE® on murine adipose stem cells - Francisca L.A. Cardoso; Letícya L.S. Soares; Danielle B.A. Silva; Napoleão M. Argôlo Neto; Edson C. Silva Filho; Adalberto S. Silva; Dayseanny O. Bezerra; Maria S.P. Cruz; Felipe C. Nunes; Wanderson G.G. Melo; João M.C. Sousa; Antonielly C. Reis; et al. (Applied Clay Science, 2024)

A new method for reducing impurities in clay minerals - Joaldo S. Lopes; Marcelo L. Morais; Alan I.S. Morais; Roosevelt D.S. Bezerra; Josy A.O. Furtini; Edson C. Silva Filho (Applied Clay Science, 2024)

Antibacterial and Antibiofilm Activity of Croton urticifolius Lam. Essential Oil Via Membrane Disruption - Ellen Araújo Malveira; Aluska Kelly A. Nunes; Alexandre Lopes Andrade; Gabriel Lucas Carvalho Melo; Wildson Max Barbosa da Silva; Selene Maia de Morais; Hélcio Silva dos Santos; Leandro Bezerra de Lima; Cynthia Cavalcanti de Albuquerque; Diego Nathan do Nascimento Souza; Edson Holanda Teixeira; Mayron Alves de Vasconcelos (Current Microbiology, 2024)

Production, characterization and application of polygalacturonase produced by Lentinus tigrinus CCMB 553 - Edson Gabriel dos Santos; Sandra Aparecida de Assis; Alexsandra Nascimento Ferreira; Marcos de Almeida Bezerra; Solange Aparecida de Paula; Layla Matos Valasques; Baraquizio Braga do Nascimento Junior; Gildomar Lima Valasques Júnior (Biocatalysis and Agricultural Biotechnology, 2024)

Slow-releasing urea coated with low-trans vegetable lipids: Effects on lamb performance, nutrient digestibility, nitrogen balance, and blood parameters - Kevily H. de O.S. de Lucena; Pedro H.S. Mazza; Ronaldo L. Oliveira; Analivia M. Barbosa; José M. Perreira Filho; Rui J.B. Bessa; Susana P. Alves; Ricardo L. Edvan; Elzania S. Pereira; Mozart Fonseca; Edson C. Silva Filho; Leilson R. Bezerra (Animal Feed Science and Technology, 2024)

Iron-bearing mining reject as an alternative and effective catalyst for photo-Fenton oxidation of phenol in water - Luana Rabelo Hollanda; Joyce Azevedo Bezerra de Souza; Guilherme Luiz Dotto; Edson Luiz Foletto; Osvaldo Chiavone-Filho (Environmental Science and Pollution Research, 2024)

Effect of slow-release urea on intake, ingestive behavior, digestibility, nitrogen metabolism, microbial protein production, blood and ruminal parameters of sheep - Aline Silva; José Morais Pereira Filho; Juliana Oliveira; Kevily Lucena; Pedro Mazza; Edson Silva Filho; Ariane Nascimento; Elzânia Pereira; Antônio Vaz; Analivia Barbosa; Ronaldo Oliveira; Leilson Bezerra (Tropical Animal Health and Production, 2023)

Applying bottom ash as an alternative Fenton catalyst for effective removal of phenol from aqueous environment - Luana Rabelo Hollanda; Joyce Azevedo Bezerra de Souza; Edson Luiz Foletto; Guilherme Luiz Dotto; Osvaldo Chiavone-Filho (Environmental Science and Pollution Research, 2023)

A systematic review of energy and mass fluxes, and biogeochemical processes in seasonally dry tropical forests and cactus ecosystems - Alexandre Maniçoba da Rosa Ferraz Jardim; José Edson Florentino de Morais; Luciana Sandra Bastos de Souza; Daniela de Carvalho Lopes; Marcos Vinícius da Silva; Héliton Pandorfi; José Francisco de Oliveira-Júnior; Jhon Lennon Bezerra da Silva; Antonio José Steidle Neto; Leonor Patricia Cerdeira Morellato; João L.M.P. de Lima; Thieres George Freire da Silva (Journal of South American Earth Sciences, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Effects of Euterpe oleracea Mart. extract on Candida spp. biofilms - Larissa Lira Brito; Kátia Regina Assunção Borges; Gabriel Xavier Silva; Marcos Antonio Custódio Neto da Silva; Rita de Nazaré Silva Alves; Amanda Mara Teles; Maria do Carmo Lacerda Barbosa; Walbert Edson Muniz Filho; Geusa Felipa de Barros Bezerra; Maria do Desterro Soares Brandão Nascimen (Brazilian Journal of Microbiology, 2023)

Chemical composition determination and evaluation of the antibacterial activity of essential oils from Ruellia asperula (Mart. Ex Ness) Lindau and Ruellia paniculata L. against oral streptococci - Ariana Azevedo Vasconcelos; Idia Nara de Sousa Veras; Mayron Alves de Vasconcelos; Alexandre Lopes Andrade; Hélcio Silva dos Santos; Paulo Nogueira Bandeira; Elnatan Bezerra de Souza; Maria Rose Jane Ribeiro Albuquerque; Edson Holanda Teixeira (Natural Product Research, 2023)

Au@Ag bimetallic nanoparticles deposited on palygorskite in the presence of TiO2 for enhanced photodegradation activity through synergistic effect - Josy A. Osajima; Alexandro S. Sá; Luzia M. C. Honorio; Pollyana Trigueiro; Lucas I. F. Pinto; Joziel A. Oliveira; Marcelo B. Furtini; Roosevelt D. S. Bezerra; Ana C. S. Alcantara; Edson C. Silva-Filho (Environmental Science and Pollution Research, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

An unusual bidentate methionine ruthenium(II) complex: photo-uncaging and antimicrobial activity - Aurideia P. de Sousa; Ana C. S. Gondim; Eduardo H. S. Sousa; Mayron A. de Vasconcelos; Edson H. Teixeira; Beatriz Pinheiro Bezerra; Alejandro Pedro Ayala; Patrícia H. R. Martins; Luiz Gonzaga de França Lopes; Alda K. M. Holanda (JBIC Journal of Biological Inorganic Chemistry, 2020)

Antioxidant activity of three seaweeds from tropical reefs of Brazil: potential sources for bioprospecting - Juliane B. Vasconcelos; Edson R. T. P. P. de Vasconcelos; Vanessa Urrea-Victoria; Patrícia S. Bezerra; Thiago N. V. Reis; Adilma L. M. Cocentino; Daniela M. A. F. Navarro; Fungyi Chow; Arsenio J. Areces; Mutue T. Fujii (Journal of Applied Phycology, 2019)

How are local fish communities structured in Brazilian semiarid headwater streams? - Carlos Alberto de Sousa Rodrigues-Filho; Ronaldo César Gurgel-Lourenço; Luis Artur Valões Bezerra; Edson Fontes de Oliveira; Rafael Pereira Leitão; Danielle Sequeira Garcez; Jorge Iván Sánchez-Botero (Hydrobiologia, 2018)

Effective Removal of the Remazol Yellow GR Dye Using Cellulose Functionalized by Basic Groups - Lucinaldo S. Silva; Mateus S. Silva; Francisco J. L. Ferreira; Luciano C. B. Lima; Roosevelt D. S. Bezerra; Antônia M. G. L. Citó; Josy A. Osajima; Edson C. Silva Filho (Water, Air, & Soil Pollution, 2018)

Intake and ingestive behavior of lambs fed diets containing ammoniated buffel grass hay - Alexandre Fernandes Perazzo; Sansão de Paula Homem Neto; Ossival Lolato Ribeiro; Edson Mauro Santos; Gleidson Giordano Pinto de Carvalho; Juliana Silva de Oliveira; Higor Fábio Carvalho Bezerra; Fleming Sena Campos; José Esler de Freitas Junior (Tropical Animal Health and Production, 2017)

Molecular Modeling and Physicochemical Properties of Supramolecular Complexes of Limonene with α- and β-Cyclodextrins - Paula dos Passos Menezes; Polliana Barbosa Pereira dos Santos; Grace Anne Azevedo Dória; Bruna Maria Hipólito de Sousa; Mairim Russo Serafini; Paula Santos Nunes; Lucindo José Quintans-Júnior; Iara Lisboa de Matos; Péricles Barreto Alves; Daniel Pereira Bezerra; Francisco Jaime Bezerra Mendonça Júnior; Gabriel Francisco da Silva; et al. (AAPS PharmSciTech, 2017)

Rhizopus arrhizus and Fusarium solani Concomitant Infection in an Immunocompromised Host - João N. de Almeida Júnior; Karim Y. Ibrahim; Gilda M. B. Del Negro; Evandro D. Bezerra; Amaro N. Duarte Neto; Marjorie V. Batista; Rinaldo F. Siciliano; Mauro C. Giudice; Adriana L. Motta; Flávia Rossi; Ligia C. Pierrotti; Maristela P. Freire; et al. (Mycopathologia, 2016)

Neurophysiological Studies and Non-Motor Symptoms Prior to Ataxia in a Patient with Machado–Joseph Disease: Trying to Understand the Natural History of Brain Degeneration - José Luiz Pedroso; Edson Bor-Seng-Shu; Pedro Braga-Neto; Rodrigo Souza Ribeiro; Márcio Luiz Escorcio Bezerra; Lucila B. F. do Prado; Ilza Rosa Batista; Helena Alessi; Manoel Jacobsen Teixeira; Gilberto Mastrocola Manzano; Gilmar Fernandes do Prado; Orlando Graziani Povoas Barsottini (The Cerebellum, 2014)